2018
DOI: 10.5194/acp-18-16653-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of shipping emissions on air pollution in the Canadian Arctic and northern regions: current and future modelled scenarios

Abstract: Abstract. A first regional assessment of the impact of shipping emissions on air pollution in the Canadian Arctic and northern regions was conducted in this study. Model simulations were carried out on a limited-area domain (at 15 km horizontal resolution) centred over the Canadian Arctic, using the Environment and Climate Change Canada's on-line air quality forecast model, GEM-MACH (Global Environmental Multi-scale – Modelling Air quality and CHemistry), to investigate the contribution from the marine shippin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…More recent Arctic‐wide simulations using the Winther et al () emissions investigated the impacts of future shipping and found significant increases in ozone concentrations particularly along the northern Norwegian coast, the Barents Sea, and off the northern coast of Alaska (Law et al, ) in line with prior estimates (Dalsøren et al, ; Granier et al, ). A recent study focusing on the impacts of Canadian shipping along the NWP found limited present‐day effects on aerosols and ozone but potentially large effects based on a business as usual scenario for 2030 with up to 5% increases in ozone and 5 to 20% in PM 2.5 along shipping corridors (Gong et al, ). Browse et al () investigated the deposition of BC from future Arctic shipping in 2050 based on the scenarios from Corbett et al ().…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…More recent Arctic‐wide simulations using the Winther et al () emissions investigated the impacts of future shipping and found significant increases in ozone concentrations particularly along the northern Norwegian coast, the Barents Sea, and off the northern coast of Alaska (Law et al, ) in line with prior estimates (Dalsøren et al, ; Granier et al, ). A recent study focusing on the impacts of Canadian shipping along the NWP found limited present‐day effects on aerosols and ozone but potentially large effects based on a business as usual scenario for 2030 with up to 5% increases in ozone and 5 to 20% in PM 2.5 along shipping corridors (Gong et al, ). Browse et al () investigated the deposition of BC from future Arctic shipping in 2050 based on the scenarios from Corbett et al ().…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…There may be an increase in future pollution emissions within the ABZ given the likely increase in wildfires, agricultural fires, and anthropogenic activities (e.g., shipping, oil and natural gas extraction, fishing) in the warmer and increasingly accessible ABZ (e.g., Arnold et al, ; Corbett et al, ; Gong et al, ; Hegg et al, ; Law et al, ; Marelle et al, ; McKuin & Campbell, ; Peters et al, ; Schmale et al, ). There are several international efforts that have as part of their design to observe these changes.…”
Section: Observing Chemistry and Composition Of The Abz Atmospherementioning
confidence: 99%
“…The compounds thought to be responsible for the majority of these deaths are ground level ozone, NO 2 , and particulate matter (PM). It is this realization that prompted Canada to formulate an Air Quality Health Index (AQHI) (Gillett et al 2004), which uses the concentrations of these three pollutants to define a scale (ranging from 0 to 10þ) to help Canadians understand what the air quality around them means to their health. These pollutants, along with others such as SO 2 , formaldehyde, and carbon monoxide (CO), result (directly or indirectly) from combustion.…”
Section: Air Quality At Northern Latitudesmentioning
confidence: 99%
“…Wildfires are particularly intense sources of air pollution in the spring and summer. While variable from year-to-year, there has been an increase in the number and severity of fires in Canada over the past half-century and this is expected to continue with the warming climate (Gillett et al 2004;Kirchmeier-Young et al 2017. Changing fire regimes in Canada's boreal forests are expected to result in increasing fire frequency and severity (Veraverbeke et al 2017) as well as a northward march in large fires with associated impacts to air quality, human health and decreased carbon storage (Bond-Lamberty et al 2007;Brandt 2009;Kurz et al 2013).…”
Section: Air Quality At Northern Latitudesmentioning
confidence: 99%
See 1 more Smart Citation